Borboletas frugívoras (Lepidoptera: Nymphalidae) do centro oeste do Rio Grande do Sul, Brasil - Paz, Ana Luiza Gomes (2013)
Fragmentation and habitat loss caused by human activities are the main threats to biodiversity. In Rio Grande do Sul State (RS), mainly in the Pampa biome in Southern State, the growing demand for production and consequent expansion of agriculture and forestry activities plus the lack of protection, increased its vulnerability. The fruitfeeding butterflies comprehend about 50% of the Nymphalidae species in neotropical forests. They are attracted and sampled with bait traps and consist of good tools for environmental monitoring. Additionally, temporal studies of this guild can help planning studies in areas not yet inventoried. This work aims to provide a list of fruitfeeding butterfly species of Midwestern of RS State and analyzed the temporal variation in richness, abundance and species composition. In parallel, we updated the regional Satyrini species list based on field studies (net sampling) and literature, and verified the influences of spatial and environmental variables on the species distribution in southern Brazil. This study was conducted at the municipalities of Jaguari, São Francisco de Assis and São Vicente do Sul, in Pampa biome, southern Brazil. Fruit-feeding butterflies were sampled bimonthly with the use of bait traps from January 2010 to December 2011, in nine sampling sites, where microclimatic variables were also measured. At these sites, the Satyrini butterflies were sampled with entomological net, from January 2010 to January 2011. After 2160 traps/days, 3288 individuals, belonging to 44 species and subspecies, were registered. Satyrinae family showed the greater number of species (57%), followed by Biblidinae (23%), Charaxinae (18%) and Nymphalinae (2%). Narope panniculus Stichel 1904 is new record for the RS State. Thirty seven species and 3822 individuals were used in temporal analyses. The results showed no significant seasonal pattern neither species richness differences among seasons, despite the register of temporal variation in the fruit-feeding butterflies assemblages studied. The total abundance was influenced by the subfamily Satyrinae abundance. The rare species played an important role in the composition of this community. Temperature, relative humidity and luminosity were the microclimate variables that contributed more in the assemblages structuring. For the 40 Satyrini species analyzed, differences in temperature, phytoecological region and spatial position proved to affect their distribution in southern Brazil. The Midwestern of RS State harbors a rich and peculiar fauna of fruit-feeding butterflies that should be preserved. It is important to create incentives for sustainable land use and public policies aiming biodiversity conservation to ensure the survival of species and their environments, especially in areas that are not legally protected.